Pelatihan EdPuzzle sebagai Media Pembelajaran Interaktif bagi Guru SMPN 1 Sungguminasa - Andi Afrinaramadhani Hatta; Nurhayani H. Muhiddin; St. Mutia Alfiyanti Muhiddin; Putri Damayanti; Amalia Rahmadani (Program Studi Pendidikan IPA Fakultas MIPA Universitas Negeri Makassar, 2026)
The rapid development of digital technology requires teachers to integrate interactive learning media into classroom instruction. However, many teachers still lack understanding of technology-based learning tools, particularly Edpuzzle as an interactive video-learning platform. Therefore, this community service program aimed to help teacher to have knowledge and skill in using EdPuzzle as an interactive learning medium. The activity was conducted at SMPN 1 Sungguminasa through preparation, implementation, and evaluation stages. The training methods included lectures, demonstrations, question-and-answer sessions, and hands-on practice. The program began with an introduction to EdPuzzle, followed by training on creating interactive learning videos. Participants then independently developed 5–7-minute interactive videos based on their respective subjects. Evaluation was carried out through observation and participant response questionnaires. The results showed that the training was successfully implemented and received positive responses from participants. Most participants stated that the training improved their understanding, skills, and motivation in utilizing educational technology. This activity is expected to enhance teachers’ pedagogical competence and digital literacy while supporting more engaging, interactive, and student-centered learning experiences.